Towards a Theory of Claim Making: Bridging Access and Property Theory. Issue 2 (1st February 2020) - Kronenburg García, Angela; van Dijk, Han
Abstract: This article proposes a framework for studying and understanding how people make claims to land and other natural resources. We argue that a focus on claim-making practices of actors (individuals, groups, institutions, companies, the state), and the processes of appropriation, accessing and contestation that come along with it, best responds to Sikor and Lund's call to examine "the grey zone" between access and property. We identify and discuss three practices of claim making: "grounding claims" is the practice of inscribing or altering the landscape with visible markers connoting ownership; "talking claims" is when speech is used strategically to make, justify and contest claims; and "representing claims" is when claims are represented on material objects (maps, title deeds) that are detached from the resource. We contribute to debates on enclosure, large-scale land acquisitions and resource grabbing by providing a lens of claim making through which these processes can be conceptualized.